Combined liver‐kidney transplantation for primary hyperoxaluria type I in children: Single Center Experience. (26th November 2018) - Kotb, Magd A.; Hamza, Alaa F.; Abd El Kader, Hesham; El Monayeri, Magda; Mosallam, Dalia S.; Ali, Nazira; Basanti, Christine William Shaker; Bazaraa, Hafez; Abdelrahman, Hany; Nabhan, Marwa M.; Abd El Baky, Hend; El Sorogy, Sally T. Mostafa; et al.
Abstract: Primary hyperoxalurias are rare inborn errors of metabolism with deficiency of hepatic enzymes that lead to excessive urinary oxalate excretion and overproduction of oxalate which is deposited in various organs. Hyperoxaluria results in serious morbid‐ity, end stage kidney disease (ESKD), and mortality if left untreated. Combined liver kidney transplantation (CLKT) is recognized as a management of ESKD for children with hyperoxaluria type 1 (PH1). This study aimed to report outcome of CLKT in a pediatric cohort of PH1 patients, through retrospective analysis of data of 8 children (2 girls and 6 boys) who presented by PH1 to Wadi El Nil Pediatric Living Related Liver Transplant Unit during 2001‐2017. Mean age at transplant was 8.2 ± 4 years. Only three of the children underwent confirmatory genotyping. Three patients died prior to surgery on waiting list. The first attempt at CLKT was consecutive, and despite initial successful liver transplant, the girl died of biliary peritonitis prior to scheduled renal transplant. Of the four who underwent simultaneous CLKT, only two survived and are well, one with insignificant complications, and other suffered from abdominal Burkitt lymphoma managed by excision and resection anastomosis, four cycles of rituximab, cyclophosphamide, vincristine, and prednisone. The other two died, one due to uncontrollable bleeding within 36 hours of procedure, while the other died awaiting renal transplant after loss of renal graft to recurrent renal oxalosis 6 months post‐transplant. PH1 with ESKD is a rare disease; simultaneous CLKT offers good quality of life for afflicted children. Graft shortage and renal graft loss to oxalosis challenge the outcome.